(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study traces the historical development of technologies in the field of artificial intelligence (AI). The relevance of the topic stems from the subsequent rapid development and implementation of computer technologies in various fields of human knowledge. Nowadays, the development of AI, as a leading computer technology in the last decade, creates unceasing interest among specialists in the field and the scientific community, given that the boundaries of its application are immense. The aim of this study is to trace the historical development of technologies in the field of artificial intelligence, using patent statistics as a measure of innovative creativity. In this regard, by applying empirical methods (comparison method, graphical method) and historical approach to analyzing data on the number of patented inventions through the Patent Cooperation Treaty (PCT), administered by the World Intellectual Property Organization (WIPO), the evolutionary development of artificial intelligence is illustrated. As a result of the study, the leading countries in which the inventive capacity in the selected technological field is concentrated are identified. The main conclusions we reached identify nine leading countries, in which 94.68% of the patent activity in the field of AI is concentrated for the period from 1980 to 2023- and 2.75-times higher research activity in 2022 compared to 2010. Despite the data, the Government and Industry sectors do not invest the necessary efforts in AI research (the Education sector conducts 81.07% of the research), which predetermines their inability to take advantage of the advantages that AI can generate.